Budget impact analysis of antiretroviral less drug regimen simplification in HIV-positive patients on the Italian National Health Service - Restelli U; Andreoni M; Antinori A; Bonfanti M; Di Perri G; Galli M; Lazzarin A; Rizzardini G; Croce D (Dove Medical Press, 2014)
Umberto Restelli,1,2 Massimo Andreoni,3 Andrea Antinori,4 Marzia Bonfanti,2 Giovanni Di Perri,5 Massimo Galli,6 Adriano Lazzarin,7 Giuliano Rizzardini,8,9 Davide Croce1,2 1Department of Community Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa; 2Centro di Ricerca in Economia e Management in Sanità e nel Sociale (CREMS), Università Carlo Cattaneo – LIUC, Castellanza (VA), Italy; 3Clinical Infectious Diseases, Tor Vergata University (PTV), Rome, Italy; 4Clinical Department, National Institute for Infectious Diseases "L. Spallanzani," Rome, Italy; 5Department of Medical Sciences, Infectious Diseases, Amedeo di Savoia Hospital, Turin, Italy; 6Third Division of Infectious Diseases, "Luigi Sacco" Hospital, Milan, Italy; 7Department of Infectious Diseases, San Raffaele Scientific Institute, Milan, Italy; 8First and Second Divisions of Infectious Diseases, "Luigi Sacco" Hospital, Milan, Italy; 9School of Clinical Medicine, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa Background: Deintensification and less drug regimen (LDR) antiretroviral therapy (ART) strategies have proved to be effective in terms of maintaining viral suppression in human immunodeficiency virus (HIV)-positive patients, increasing tolerability, and reducing toxicity of antiretroviral drugs administered to patients. However, the economic impact of these strategies have not been widely investigated. The aim of the study is to evaluate the economic impact that ART LDR could have on the Italian National Health Service (INHS) budget. Methods: A budget impact model was structured to assess the potential savings for the INHS by the use of ART LDR for HIV-positive patients with a 3 year perspective. Data concerning ART cost, patient distribution within different ARTs, and probabilities for patients to change ART on a yearly basis were collected within four Italian infectious diseases departments, providing ART to 13.7% of the total number of patients receiving ART in Italy. Results: The LDR investigated (protease inhibitor-based dual and monotherapies) led to savings for the hospitals involved when compared to the "do nothing" scenario on a 3 year basis, between 6.7% (23.11 million €) and 12.8% (44.32 million €) of the total ART expenditures. The mean yearly cost per patient is reduced from 9,875 € in the do nothing scenario to a range between 9,218 € and 8,615 €. The use of these strategies within the four departments involved would have led to a reduction of ART expenditures for the INHS of between 1.1% and 2.1% in 3 years. Conclusion: ART LDR simplification would have a significant impact in the reduction of ART-related costs within the hospitals involved in the study. These strategies could therefore be addressed as a sustainable answer to the public financing reduction observed within the INHS in the last year, allowing therapies to be dispensed without affecting the quality of the services provided. Keywords: antiretroviral therapy, Italy, budget impact model, monotherapy, dual therapy, cost